2006
DOI: 10.1017/s0016672306008329
|View full text |Cite
|
Sign up to set email alerts
|

Upper limit of the rate and per generation effects of deleterious genomic mutations

Abstract: Unbiased or upper limit estimates of the rate (U) of genomic mutations to mildly deleterious alleles are crucial in genetic and conservation studies and in human health care. However, only a few estimates of the lower bounds of U are available. We present a fairly robust estimation that yields an upper limit of U and a nearly unbiased estimate of the per generation fitness decline due to new deleterious mutations. We applied the approach to three species of the freshwater microcrustacean Daphnia and revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…In general, mutations are deleterious, so these adaptive alleles are likely to arise in close linkage with deleterious sites. Estimates of the deleterious mutation rate range from 0.07 to 0.1 mutations per generation per genome in Arabidopsis (Ossowski et al 2010;Rutter et al 2012), 0.4 in Caenorhabditis elegans (Denver et al 2004), and upper limits of 0.6-0.8 in Daphnia pulex (Lynch et al 1998;Deng et al 2006). Further empirical estimates of the distribution of fitness effects in facultative sexuals, and partially selfing organisms, will be important to determine the effect of advantageous-deleterious interactions on the evolution of mating systems.…”
Section: Discussionmentioning
confidence: 99%
“…In general, mutations are deleterious, so these adaptive alleles are likely to arise in close linkage with deleterious sites. Estimates of the deleterious mutation rate range from 0.07 to 0.1 mutations per generation per genome in Arabidopsis (Ossowski et al 2010;Rutter et al 2012), 0.4 in Caenorhabditis elegans (Denver et al 2004), and upper limits of 0.6-0.8 in Daphnia pulex (Lynch et al 1998;Deng et al 2006). Further empirical estimates of the distribution of fitness effects in facultative sexuals, and partially selfing organisms, will be important to determine the effect of advantageous-deleterious interactions on the evolution of mating systems.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, nucleotide diversity at the sequence level is 4N e m in diploids, and thus can be used to estimate m (Deng & Lynch 1996;Kondrashov 1998;Li & Deng 2005;Deng et al 2006;Messer 2009). However, because N e is not known independently, this relationship is more useful for estimating N e and not m (Kondrashov 1998;Caballero 2006).…”
Section: Methods For Determining Mutation Ratesmentioning
confidence: 99%
“…Analogous estimators can be obtained for the case of naturally segregating inbred populations (Deng et al, 2006). For example, the estimated upper limit of U was generally no more than twice the true value under the different simulation cases (see table 1 of Deng et al, 2006). They concluded that the estimation of U and Uhs is not greatly biased.…”
Section: Introductionmentioning
confidence: 82%
“…Analogous estimators can be obtained for the case of naturally segregating inbred populations (Deng et al, 2006). Analogous estimators can be obtained for the case of naturally segregating inbred populations (Deng et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation